The goiter prevalence and urinary iodine levels among adolescents - Kutlu, Ruhuşen; Karaköse, Serdar; Güngör, Kağan; Kulaksizoğlu, Sevsen (The Turkish Journal of Pediatrics, 2011)
Endemic goiter and iodine deficiency are among the worldwide major public health problems of today. We aimed to research the goiter prevalence and the urinary iodine level of school children. In this descriptive study, 1,847 school children in Konya aged between 10 and 18 years were included. Urinary iodine level was measured. The mean value of iodine excretion in urine was 198 +/- 46.61 microg/L. In 40 students (2.2%), the urinary iodine level was < 100 microg/L. Six of these students (0.3%) had moderate iodine deficiency. Thyroid hyperplasia was found with palpation method in 128 students (6.9%). Ultrasonographically, five female students had solid nodule, and one male student had multiple nodules. In our study, no severe iodine deficiency was found. According to the results of our study, the mandatory iodization program in Konya has been conducted successfully.